The current state of information management and knowledge management in the Malaysian construction industry - Noordin, Mohamad Fauzan; Burhanuddin , Long Ahmad; Kanaa , Ahmad (INSI Publications, 2012)
The construction industry generates a vast amount of information and knowledge that may need to be organized more efficiently to facilitate dissemination and utilization by the communities of practitioners. The objective of this paper is to explore the state and extent of information management and knowledge management in the Malaysian construction industry. This research was carried out by fielding survey questionnaires to personnel of construction companies, consultancies, and project management firms. Based on survey results, some aspects of information management are discussed. The article concludes with recommendations on requisites that should be in place prior to implementation of knowledge management in construction companies.